Emotion dysregulation, bullying, and suicide behaviors in adolescents - Anthony Kennedy; Amy M. Brausch (Journal of Affective Disorders Reports, 2024)
Background: : Among adolescents, rates for suicide attempts and non-suicidal self-injury (NSSI) remain high. Adolescents also often experience bullying, which has been found to associate with increased risk of suicide attempts and NSSI. Emotion regulation difficulties are associated with both bullying victimization and self-harm behaviors in adolescents. Aims: : The current study examined the relationship between emotion dysregulation and suicide attempts and NSSI with bullying as a moderating factor. Method: : High school students (n = 804) completed self-report measures on emotion regulation difficulties, suicide attempts, nonsuicidal self-injury, and past-year bullying experiences. Results: : Moderation analyses found that the relationships between multiple emotion dysregulation dimensions and suicide attempts were significant regardless of bullying experience, but the relationship was stronger when bullying was present. For NSSI, bullying only moderated the relationships between nonacceptance of emotions, limited emotion regulation strategies and NSSI, with stronger associations when bullying was present. Limitations: : Different types of bullying were not assessed, all measures were self-report, and the community sample had relatively low clinical severity. Conclusion: : Results indicate that poor emotion regulation and bullying victimization associate with greater frequencies of suicidal and nonsuicidal behaviors. These findings point to the need for self-harm prevention programs to address both bullying and emotion regulation skills.